Foundational and practical aspects of resource analysis : Third International Workshop, FOPARA 2013, Bertinoro, Italy, August 29-31, 2013, Revised Selected Papers - Pena, Ricardo; Dal Lago, Ugo (Lecture Notes in Computer Science, 2014)
This book constitutes the proceedings of the Third International Workshop on Foundational and Practical Aspects of Resource Analysis, FOPARA 2013, held in Bertinoro, Italy, in August 2013. The 9 papers presented in this volume were carefully reviewed and selected from 12 submissions. They deal with traditional approaches to complexity analysis, differential privacy, and probabilistic analysis of programs.